AND WHEN THE CHILD DOES NOT MEET THE SCHOOL'S EXPECTATIONS? REFLECTIONS ON RELATIONSHIP WITH THE FAMILY IN THE SEARCH FOR A DIAGNOSIS - Araujo, Luciana Aparecida de [UNESP]; Anjos, Cleriston Izidro dos; Pereira, Fabio Hoffmann (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The objective of this article is to understand the way in which the school has responded to children diagnosed with Attention Deficit Hyperactivity Disorder (ADHD), from the point of view of pedagogical work and the relationship with the family. Through a bibliographic research and a study of a case, it brings the story of an 8-year-old child with a diagnostic hypothesis of ADHD. Data was collected through the mother's narrative and recorded in a field journal. The results reveal that the student's task demanded by the school goes beyond cognitive aspects and content learning, involving an adult's expectation about a way of being school. It is concluded that the school must embrace diversity and difference, so as not to incur in strategies for the defense and no responsibility of pedagogical work.
Keywords: Education; School difficulties; Diagnosis; ADHD; Family-school relationship